A bibliometric investigation into the intellectual milieu of research on consumer socialization of children - Nehajoan Panackal; Adya Sharma; Sonica Rautela (Cogent Business & Management, 2024)
Studies on consumer socialization delve into how customers acquire an interest in a product or service. These studies attempt to comprehend customer attitudes, perceptions, and behaviors towards a product or service as a result of diverse social interactions. Children are a vital part of this process. Family members, classmates and friends, the media, school, other institutions, and cultures all impact children's socialization process, resulting in consumption decisions. A glance at the literature on consumer socialization of children throughout the last five decades shows how related literature has evolved over a period of time. Consumer socialization is vital in the market and consumer research. However, there is a need to offer a more comprehensive picture of the work that scholars worldwide have done in this sector. Bibliometric analysis is a common tool for tracing the evolution of literature over the previous decades. The researchers in this study employed bibliometric analysis to assess a study done in consumer socialization. The current study used bibliometric analysis to discover the most frequently cited papers, journals, nations, organizations, and authors in the ethics and higher education literature. In addition, the study seeks to comprehend new research areas in consumer socialization.
Keywords: 650; Socialisation; children; bibliometric analysis; consumer socialization